Smoking, Income and Subjective Well-Being: Evidence from Smoking Bans - Abel Brodeur (Institute for the Study of Labor (IZA), 2013)
This paper investigates the effects of local smoking bans on different out-comes using county and time variation over the last 20 years in the US. First, I find no evidence that local smoking bans in bars, restaurants and workplaces decrease the prevalence of smoking. The estimates are very small and not statistically significant. Well-being is also affected by these policies: public smoking bans make smokers who do not quit more satisfied with their life. I verify the robustness of this result throughout, and validate my findings with two distinct data sources. I discuss and test the mechanisms behind this seemingly paradoxical relationship. The evidence suggests that smokers adapt to this policy since the impact on satisfaction is negative just before the implementation and positive afterward. Last, I find evidence that smokers do not favor the implementation of smoking bans. Yet, once they are exposed to a public smoking ban, they are less-opposed to those policies. Together the evidence suggests that current smokers are time-inconsistent and benefit from smoking policies.
Keywords: D62; H51; I18; I38; 330; adaptation; addiction; smoking policies; subjective well-being; time-inconsistency